2020
DOI: 10.1002/cphc.202000568
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Roughness of Porphyrin Thin Films with X‐ray Photoelectron Spectroscopy

Abstract: Thin-film growth of molecular systems is of interest for many applications, such as for instance organic electronics. In this study, we demonstrate how X-ray photoelectron spectroscopy (XPS) can be used to study the growth behavior of such molecular systems. In XPS, coverages are often calculated assuming a uniform thickness across a surface. This results in an error for rough films, and the magnitude of this error depends on the kinetic energy of the photoelectrons analyzed. We have used this kinetic-energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…This observation indicates either a disordered monolayer or a monolayer consisting of tilted molecules at the angle in which there is no dependence with the photon polar incidence angle (54.7°) . Recently, we have used angle-resolved photoelectron spectroscopy to study the growth of Co-MCTPP on TiO 2 (110), and we found that monolayer deposition results in a disordered layer that grows in three dimensions . Thus, the NEXAFS measurements corresponding to the MCTPP monolayer could indicate a disordered monolayer.…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This observation indicates either a disordered monolayer or a monolayer consisting of tilted molecules at the angle in which there is no dependence with the photon polar incidence angle (54.7°) . Recently, we have used angle-resolved photoelectron spectroscopy to study the growth of Co-MCTPP on TiO 2 (110), and we found that monolayer deposition results in a disordered layer that grows in three dimensions . Thus, the NEXAFS measurements corresponding to the MCTPP monolayer could indicate a disordered monolayer.…”
Section: Results and Discussionmentioning
confidence: 90%
“…30 Recently, we have used angle-resolved photoelectron spectroscopy to study the growth of Co-MCTPP on TiO 2 (110), and we found that monolayer deposition results in a disordered layer that grows in three dimensions. 31 Thus, the NEXAFS measurements corresponding to the MCTPP monolayer could indicate a disordered monolayer. Hence, under the assumption of no preferred azimuthal orientation, our NEXAFS data suggest that as we go from low coverages to monolayer coverages, the number of molecules with the macrocycle tilted away from the surface increases as there is a transition from flat-lying molecules to a disordered layer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This requires us to correct for the moderate changes in attenuation of the Ti 3p signal as the emission angles change from −20 to 60°, while the E -field polar angle relative to the surface normal changes from 10 to 90°. We did this by extrapolating the attenuation of the Ti 3p signal by the phosphonic acid monolayer we observed at 100 eV kinetic energy to a kinetic energy of 260 eV, based on literature data. This results in a correction factor of 1.6 for the inelastic mean free path (IMFP).…”
Section: Methodsmentioning
confidence: 99%
“…Coverages were calculated in two different ways: for the initial depositions, coverages were calculated based on the C 1s-to-Ti 2p ratios. For the deposited amounts (<4 ML), attenuation of the Ti 2p substrate signal is only modest (<40%) and thus any deviation from perfect layer-by-layer growth should only have a small effect on the calculated coverages. , After annealing to 525 K at 20 K/min, the multilayers have desorbed and only the monolayer remains. The heating rate was chosen low enough to achieve equilibrium, such that our two different starting points (A on B and B on A) resulted in almost identical remaining monolayers.…”
Section: Methodsmentioning
confidence: 99%